Return and Volatility Analysis of the Islamic Stock Index on Generation Z’s Investment Flow Impr - Nurul Febryana; Ahadiah Agustina; Novi Yanti Sandra Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the relationship between the performance of Islamic stock indices, particularly return and volatility, and Generation Z’s investment behavior in Indonesia. This research is motivated by the increasing participation of young investors in digital-based investment activities aligned with Islamic financial principles. Unlike previous studies that tend to rely on perception-based measures, this study emphasizes the distinction between objective financial indicators and subjective investor behavior. This research adopts a quantitative explanatory approach by combining secondary data in the form of Islamic stock index returns and volatility with primary data measuring Generation Z’s investment behavior through questionnaires. Data analysis is conducted using multiple linear regression. The findings indicate that volatility has a significant influence on Generation Z’s investment behavior, while return does not show a significant effect. These results suggest that Generation Z investors are more sensitive to market risk and uncertainty than to potential returns. This study contributes to the development of Islamic behavioral finance literature and provides practical implications for enhancing adaptive Islamic financial literacy strategies.